Effectiveness Analysis of Claw Designs on the URA Platform for the First Stage of the Brazilian Robotics Olympics - Brandt, Guilherme; Alsina, Pablo Javier; Gonçalves, Luiz Marcos Garcia (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2024: Anais do XVI Simpósio Brasileiro de Robótica e XV Workshop de Robótica na Educação, 2024)
The usage of robotics as a supporting tool to educational activities in Brazil has gained traction with the popularization of both consumer-grade 3D printers and the promotion of events such as the Brazilian Robotics Olympiad (OBR). To compete in such contest, students need to design and make their own robots, which should be able to solving rescue tasks that most often require picking up a ball on some irregular arena ground. This paper analyzes different claw designs, both active (a design that uses a motor) and passive (a design that does not use a motor) in order to evaluate the abilities and capabilities of each design, on the One Robot per Student (URA) platform. We then propose a passive design with comparable effectiveness to the active design in order to reduce the complexity of robot construction. Experiments show that the approach reduces failure points and facilitates the process of teaching a lay-student on building a robot capable of surpassing the challenges proposed by the rescue line challenge from OBR at its fundamental level (one).